Head and Gaze Orientation in Hemispheric Image Viewing - Kangas, Jari; Špakov, Oleg; Raisamo, Roope; Koskinen, Olli; Järvenpää, Toni; Salmimaa, Marja (Frontiers in Virtual Reality, 2022)
Head mounted displays provide a good platform for viewing of immersive 360 degree or hemispheric images. A person can observe an image all around, just by turning his/her head and looking at different directions. The device also provides a highly useful tool for studying the observer's gaze directions and head turns. We aimed to explore the interplay between participant's head and gaze directions and collected head and gaze orientation data while participants were asked to view and study hemispheric images. In this exploration paper we show combined visualizations of both the head and gaze orientations and present two preliminary models of the relation between the gaze and the head orientations. We also show results of an analysis of the gaze and head behavior in relation to the given task/question.